Dyslipidaemia, Chronic Kidney Disease and Diabetes Mellitus: A Triple Threat to Cardiovascular Health - Ann S. Forrest; Priyanka Majety; Stéphanie B. Mayer; Om P. Ganda (Diabetes, Obesity and Metabolism, 2026)
ABSTRACT Diabetes mellitus (DM) and chronic kidney disease (CKD) frequently coexist and together create a ‘triple threat’ with dyslipidaemia, enhancing the risk for cardiovascular morbidity and mortality. Diabetic kidney disease (DKD) leads to altered lipid metabolism through insulin resistance, inflammation and oxidative stress resulting in an atherogenic lipid profile that accelerates atherosclerosis and vascular dysfunction. While statins remain the cornerstone of lipid‐lowering therapy, their cardiovascular benefits decline in advanced CKD. Combination therapy with ezetimibe and newer agents, including PCSK9 inhibitors and bempedoic acid, has shown further cardiovascular risk reduction in CKD. Emerging therapies targeting alternative pathways may address residual lipid abnormalities not corrected by traditional treatments but require longer‐term outcome data in people with DM and CKD. As the prevalence of both conditions rises, applying multifaceted lipid‐lowering strategies may yield the greatest reduction in cardiovascular events and improve survival among this vulnerable population.